2012
DOI: 10.1016/j.cmet.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Regulates Cellular Iron Homeostasis through Tristetraprolin

Abstract: SUMMARY Iron is an essential cofactor with unique redox properties. Iron regulatory proteins 1 and 2 (IRP1/2) have been established as important regulators of cellular iron homeostasis, but little is known about the role of other pathways in this process. Here we report that the mammalian target of rapamycin (mTOR) regulates iron homeostasis by modulating transferrin receptor 1 (TfR1) stability and altering cellular iron flux. Mechanistic studies identify tristetraprolin (TTP), a protein involved in anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(175 citation statements)
references
References 41 publications
12
154
0
Order By: Relevance
“…[23][24][25][26][27][28][29] Normally, an increase in cellular iron inactivates iron regulatory proteins and decreases TfR1 mRNA levels. We observed increased TfR1 mRNA levels and a concurrent cellular iron overload with HIV infection, which suggests that HIV infection is driving the upregulation of TfR1 independent of other cellular iron regulatory machineries.…”
Section: Relationship Among Iron Hiv and Art 309mentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Normally, an increase in cellular iron inactivates iron regulatory proteins and decreases TfR1 mRNA levels. We observed increased TfR1 mRNA levels and a concurrent cellular iron overload with HIV infection, which suggests that HIV infection is driving the upregulation of TfR1 independent of other cellular iron regulatory machineries.…”
Section: Relationship Among Iron Hiv and Art 309mentioning
confidence: 99%
“…Nonetheless, the Tfrc transcript was stabilized in the ZFP36L3-deficient TSCs, its 3′UTR contains two highly conserved and closely spaced 8-mer potential ZFP36L3-binding sites, and it was highly enriched in the ZFP36L3 immunoprecipitates. It was previously identified as a possible direct TTP target in other tissues (Bayeva et al, 2012). These data suggest that the profound decrease in Tfrc mRNA levels might be a secondary effect of ZFP36L3 deficiency resulting in inhibition of transcription of Tfrc in the placenta.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have reported that increased intracellular copper levels suppressed mTOR signaling [44], and that copper treatment down regulated mTOR signaling [45]. With respect to increased serum Tf levels, the mTOR signaling pathway modulates Tf uptake [10], and mTOR regulates iron homeostasis through the Tf receptor [9]. Additionally, the Tf receptor may be useful for measuring intracellular changes in mTOR activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced reactive oxygen species [7] enhanced mTOR [5], and that mTOR inhibitor everolimus blocked the enhanced phosphorylation of mTOR [6]. Moreover, copper-related antioxidants, such as ceruloplasmin (Cp) [8] and iron-related transferrin (Tf) [9] are closely related to mTOR signaling. For example, Cp expression mas related to activation of mTOR pathway [8].…”
Section: Introductionmentioning
confidence: 99%